95. Edmund Gabriel, St Paul de Loanda, to Rev Arthur Tidman [Mission House, Blomfield Street, London]
Thanking the directors of the London Missionary Society for their expressions of gratitude to him for the assistance that he offered Livingstone while he was in Loanda [Luanda, Angola], and expressing his own interest in and support for Livingstone's work.